The Principles of Matter (Global Journal of Science Frontier Research, 2025)
Matter is any substance that has mass and energy Matter has a minimum energy requirement Matter tends to share energy with other matter to form a system of minimum energy formation Matter moves because of this tendency Relevant issues are discussed Examples and evidence are listed to show how the Principles of Matter work
Keywords: matter; energy; minimum energy requirement; energy sharing; the law of minimum energy formation